2015
DOI: 10.1038/ncomms7367
|View full text |Cite|
|
Sign up to set email alerts
|

The reverse evolution from multicellularity to unicellularity during carcinogenesis

Abstract: Theoretical reasoning suggests that cancer may result from a knockdown of the genetic constraints that evolved for the maintenance of metazoan multicellularity. By characterizing the whole-life history of a xenograft tumour, here we show that metastasis is driven by positive selection for general loss-of-function mutations on multicellularity-related genes. Expression analyses reveal mainly downregulation of multicellularity-related genes and an evolving expression profile towards that of embryonic stem cells,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
122
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(138 citation statements)
references
References 64 publications
(95 reference statements)
16
122
0
Order By: Relevance
“…In essence, both of these cancers are actually behaving as autonomous organisms; their relationships with their hosts may shed light on the evolution of host-pathogen interactions (24), and they may even be taken as asexually duplicated unicellular pathogens (25). By analysis of experimental evolution, this hypothesis is supported by current results from Chen et al (26).…”
Section: General Characteristics Of Various Kinds Of Cancers Are Uncomentioning
confidence: 76%
See 1 more Smart Citation
“…In essence, both of these cancers are actually behaving as autonomous organisms; their relationships with their hosts may shed light on the evolution of host-pathogen interactions (24), and they may even be taken as asexually duplicated unicellular pathogens (25). By analysis of experimental evolution, this hypothesis is supported by current results from Chen et al (26).…”
Section: General Characteristics Of Various Kinds Of Cancers Are Uncomentioning
confidence: 76%
“…We suggest that most cancers can be transmitted mechanically if there are enough opportunities to be passed on to a suitable host. Strong evidence from recent studies on the reverse evolution from multicellularity to unicellularity supports this hypothesis (26). The parallels between these infectious cancers (transmission via immune evasion) will be discussed below in the light of parasitic infections.…”
Section: General Characteristics Of Various Kinds Of Cancers Are Uncomentioning
confidence: 95%
“…Another question is the role that cancer plays in development (25) and the transition from unicellular to multicellular behavior, and the role that cancer has played as an evolutionary variable (33). Because we show that up-expressed nonsubstituted genes and highly substituted genes are predominantly ancient genes, perhaps cancer represents a return to unicellularity that is represented by these crucial and ancient genes, with cancer allowing substitutions in, or abandoning higher-level genes associated with, multicellular cooperation (34). Clearly, with our limited data set, in this paper, we cannot address this question in a deeply quantitative way, but we hope we can point to different ways of viewing how cancer has influenced the process of development and its possible ancient origins.…”
Section: Discussionmentioning
confidence: 92%
“…It has been reported that disruption of genes tied to multicellularity confers advantages to malignant tumor clones (12), the expression of highly conserved genes is a feature of drug resistance in tumor cells (7), and there is global convergent activation in tumors of transcriptional programs associated with dedifferentiation (12,13). These findings suggest deeper understanding of the differences in the expression and regulation of ancient unicellular and more recently evolved multicellular gene sets during malignant transformation will be crucial for uncovering the molecular basis of common tumor phenotypes and will provide new targets and strategies for cancer therapy.…”
mentioning
confidence: 99%